Complete mitochondrial genome of the Western Capercaillie Tetrao urogallus (Phasianidae, Tetraoninae) - Aleix-Mata, Gaël; Ruiz-Ruano, Francisco J.; Pérez, Jesús M.; Sarasa, Mathieu; Sánchez, Antonio (Zootaxa, 2019)
The Western Capercaillie (Tetrao urogallus) is a galliform bird of boreal climax forests from Scandinavia to eastern Siberia, with a fragmented population in southwestern Europe. We extracted the DNA of T. urogallus aquitanicus and obtained the complete mitochondrial genome (mitogenome) sequence by combining Illumina and Sanger sequencing sequence data. The mitochondrial genome of T. urogallus is 16,683 bp long and is very similar to that of Lyrurus tetrix (16,677 bp). The T. urogallus mitogenome contains the normal 13 protein-coding genes (PCGs), 22 transfer RNAs, 2 ribosomal RNAs, and the control region. The number, order, and orientation of the mitochondrial genes are the same as in L. tetrix and in other species of the same and other bird families. The three domains of the control region contained conserved sequences (ETAS; CSBs), boxes (F, E, D, C, B, BS box), the putative origin of replication of the H-strand (OH) and bidirectional promoters of translation (LSP/HSP).